PENERAPAN METODE DARING DI SEKOLAH DASAR DI INDONESIA PADA MASA PANDEMI COVID-19 - Euis Eka Pramiarsih (Lembaga Penelitian Universitas Langlangbuana, 2020)
At the beginning of 2020, the world experienced a global disaster which is Covid-19 Pandemic (Coronavirus Disease 2019). This disease is transmitted through droplets of body fluids from the infected. Governments of many countries in the world provide solutions in the form of wearing masks and social distancing. This has great impact on human social activities including elementary school education. To overcome this, online learning methods is implemented (daring) which have a number of advantages and disadvantages compared to offline (luring) methods. This study aims to identify the implementation of online learning in elementary school students due to the COVID-19 pandemic. The study uses literature research by gathering data with documentation techniques that are filtering for data about relevant matters from a variety of documents, books, magazines, and news. The criteria for selected articles and news are discussion of the impact of COVID-19 and online learning in elementary schools. The results in this study indicate that the impact of COVID-19 on the implementation of online learning in elementary schools can be carried out quite well if there is good collaboration between teachers, students and parents in online learning.